Cross-linked amino type polybenzimidazole composite membrane for vanadium battery and preparation method of cross-linked amino type polybenzimidazole composite membrane

Through the preparation of cross-linked amino polybenzimidazole composite film, the cross-linked structure and acid-base interaction are used to solve the problems of low proton conductivity and decreased mechanical strength of polybenzimidazole under non-wet conditions, achieving high efficiency The proton conduction and mechanical stability are improved, which improves the voltage and Coulomb efficiency of vanadium batteries.

CN119119376AInactive Publication Date: 2024-12-13HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411605512.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polybenzimidazole has low proton conductivity under non-wet conditions, and excessive doping of acid will lead to a decrease in the mechanical strength of the membrane, making it difficult to achieve high proton conductivity and good tensile strength at the same time.

Method used

The preparation method of cross-linked amino polybenzimidazole composite membrane is adopted to form a cross-linked structure through substitution reaction and double bond polymerization, combining the acid-base interaction between alkaline functional monomers and acids, and improving proton conductivity and mechanical stability.

Benefits of technology

The voltage efficiency and Coulomb efficiency of vanadium batteries are improved, while the mechanical stability and tensile strength of the membrane are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119376A_ABST
    Figure CN119119376A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ion exchange membranes of all-vanadium redox flow batteries, and discloses a cross-linked amino type polybenzimidazole composite membrane for a vanadium battery and a preparation method of the cross-linked amino type polybenzimidazole composite membrane. The preparation method comprises the following steps: S1, preparing an imidazole functional monomer 1 containing double bonds; s2, preparing a functional monomer 2 containing double bonds; step S3, preparing a cross-linked amino type polybenzimidazole solution; and step S4, preparing the cross-linked amino polybenzimidazole composite membrane. The composite membrane disclosed by the invention has a cross-linked structure, so that the acid absorption rate and the proton conductivity can be improved, the voltage efficiency of the vanadium battery can be improved, and the tensile strength and the mechanical stability of the membrane can also be improved; the nitrogen heterocyclic structure in the chain segment can inhibit vanadium ion permeation and improve coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion exchange membranes for all-vanadium liquid flow batteries, and in particular to a cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries and a preparation method thereof. Background Art

[0002] Polybenzimidazole has been widely used due to its excellent high-temperature thermal stability and excellent mechanical strength, and has attracted widespread attention in the academic community. Due to its rigid nitrogen heterocyclic structure, it can act as both a proton acceptor and a proton donor, thereby promoting proton transport. However, the proton conductivity of polybenzimidazole under non-wet conditions is not satisfactory, and the voltage efficiency assembled in an all-vanadium liquid flow battery is low. At present, this problem can be effectively solved by doping free acid into the membrane, because the protonated cations in imidazole can form acid-base interactions with the acid, construct proton transport channels, and thus improve the proton conductivity of the membrane. However, due to the plasticizing effect of the acid, excessive acid doping will lead to a decrease in the mechanical strength of the membrane. Therefore, having both high proton conductivity and good tensile strength is an urgent problem to be solved. Summary of the invention

[0003] The purpose of the present invention is to provide a cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries and a preparation method thereof to solve the above problems.

[0004] The technical solution adopted by the present invention is as follows: A method for preparing a cross-linked amino-type polybenzimidazole composite membrane for a vanadium battery comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: adding 10-20 parts by weight of compound 1 and 10-20 parts by weight of imidazole compound 2 to a reactor for reaction, pouring the reactants into acetone for washing and vacuum filtering at 25° C. to obtain imidazole functional monomer 1 containing a double bond; Step S2, preparation of a functional monomer 2 containing a double bond: adding 5-10 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5-10 parts by mass of compound 1 and 10-20 parts by mass of compound 3 to a reactor for reaction, pouring the reactants into acetone for washing and vacuum filtering at 25° C. to obtain a functional monomer 2 containing a double bond; Step S3, preparation of a cross-linked amino polybenzimidazole solution: adding 1000-2000 parts by mass of a solvent and 40-80 parts by mass of amino polybenzimidazole powder to a reactor for dissolution, and then sequentially adding an imidazole functional monomer 1 containing a double bond, a functional monomer 2 containing a double bond and 2-4 parts by mass of an initiator for reaction to obtain a cross-linked amino polybenzimidazole solution; Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80° C. to dry for 18-24 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 40-60 μm.

[0005] Preferably, in step S1 and step S2, compound 1 is any one of 1-bromo-3-chloropropane, 1-bromo-4-chlorobutane, and 1-bromo-6-chlorohexane.

[0006] Preferably, the imidazole compound 2 in step S1 is any one of 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole and 5-vinylimidazole.

[0007] Preferably, the reaction conditions in step S1 are a reaction temperature of 80-150° C., a stirring speed of 300-500 rpm, and continuous reaction for 10-14 hours under condensation reflux conditions.

[0008] Preferably, compound 3 in step S2 is any one of 4-bromo-1-butene, 5-bromo-1-pentene, and 6-bromo-1-hexene.

[0009] Preferably, the reaction conditions in step S2 are reaction temperature 0-10° C., stirring speed 300-500 rpm, and reaction time 5-8 h.

[0010] Preferably, the solvent in step S3 is any one of dimethyl sulfoxide, acetone, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0011] Preferably, the initiator in step S3 is any one of azobisisobutyronitrile, azobisisoheptanenitrile, azobiscyanovaleric acid, benzoyl peroxide, and lauroyl peroxide.

[0012] Preferably, the reaction conditions in step S3 are to heat the mixture to 60-80°C for 3-6 hours, and then heat the mixture to 140-160°C for 10-16 hours.

[0013] The invention discloses a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery, which is obtained by adopting the preparation method of the cross-linked amino-type polybenzimidazole composite membrane for vanadium battery.

[0014] The beneficial effects of the present invention are:

[0015] The cross-linked amino-type polybenzimidazole composite membrane of the present invention forms a cross-linked structure through substitution reaction and double bond polymerization, and the functional monomer has an alkaline structure, which can form an acid-base interaction with the acid, thereby improving the acid absorption rate of the composite membrane, so that the membrane obtains a higher acid absorption level, thereby improving the proton conductivity of the membrane, and further improving the voltage efficiency of the vanadium battery.

[0016] The nitrogen heterocyclic structure in the cross-linked amino-type polybenzimidazole composite membrane chain segment of the present invention has positive electrical characteristics, and can inhibit the penetration of vanadium ions through the Donnan repulsion effect, thereby improving the coulomb efficiency of the vanadium battery.

[0017] The cross-linked amino-type polybenzimidazole of the present invention forms a cross-linked structure through substitution reaction and double bond polymerization, thereby improving the tensile strength of the film and improving the mechanical stability of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a diagram showing the preparation mechanism of cross-linked amino-type polybenzimidazole according to Example 1 of the present invention; Figure 2 The nuclear magnetic resonance hydrogen spectra of the imidazole functional monomer 1 containing a double bond and the functional monomer 2 containing a double bond in Example 1 of the present invention; Figure 3 The infrared spectra of the imidazole functional monomer 1 containing a double bond, the functional monomer 2 containing a double bond and the cross-linked amino-type polybenzimidazole in Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0019] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides a method for preparing a cross-linked amino-type polybenzimidazole composite membrane for a vanadium battery, comprising the following steps: Step S1, preparation of imidazole functional monomer 1 containing double bonds: 10-20 parts by mass of compound 1 and 10-20 parts by mass of imidazole compound 2 are added to a reactor for reaction, the reaction temperature is 80-150°C, the stirring speed is 300-500rpm, and the reaction is continued for 10-14h under condensation reflux conditions. The reactants are poured into acetone for washing and vacuum filtered at 25°C to obtain imidazole functional monomer 1 containing double bonds. Wherein, compound 1 is any one of 1-bromo-3-chloropropane, 1-bromo-4-chlorobutane, and 1-bromo-6-chlorohexane; imidazole compound 2 is any one of 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole, and 5-vinylimidazole.

[0021] Step S2, preparation of functional monomer 2 containing double bonds: 5-10 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5-10 parts by mass of compound 1 and 10-20 parts by mass of compound 3 are added to a reactor for reaction, the reaction temperature is 0-10°C, the stirring speed is 300-500rpm, the reaction time is 5-8h, the reactant is poured into acetone for washing and vacuum filtered at 25°C to obtain functional monomer 2 containing double bonds. Wherein, compound 1 is any one of 1-bromo-3-chloropropane, 1-bromo-4-chlorobutane, and 1-bromo-6-chlorohexane; compound 3 is any one of 4-bromo-1-butene, 5-bromo-1-pentene, and 6-bromo-1-hexene.

[0022] Step S3, preparation of cross-linked amino polybenzimidazole solution: add 1000-2000 parts by mass of solvent and 40-80 parts by mass of amino polybenzimidazole powder to the reactor to dissolve, then add double bond-containing imidazole functional monomer 1, double bond-containing functional monomer 2 and 2-4 parts by mass of initiator in sequence, heat to 60-80°C for reaction for 3-6h, then heat to 140°C-160°C for reaction for 10-16h, and obtain cross-linked amino polybenzimidazole solution. Wherein, the solvent is any one of dimethyl sulfoxide, acetone, N,N-dimethylacetamide, and N,N-dimethylformamide; the initiator is any one of azobisisobutyronitrile, azobisisoheptonitrile, azobiscyanovaleric acid, benzoyl peroxide, and lauroyl peroxide.

[0023] Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80° C. to dry for 18-24 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 40-60 μm.

[0024] Embodiment 1: comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: 10 parts by mass of compound 1-bromo-4-chlorobutane and 10 parts by mass of imidazole compound 1-vinyl imidazole are added to a reactor for reaction at a reaction temperature of 80° C. and a stirring speed of 400 rpm. The reaction is continued for 10 hours under condensation reflux conditions. The reactant is poured into acetone for washing and vacuum filtered at 25° C. to obtain imidazole functional monomer 1 containing a double bond.

[0025] Step S2, preparation of functional monomer 2 containing double bonds: 5 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5 parts by mass of compound 1-bromo-4-chlorobutane and 10 parts by mass of compound 4-bromo-1-butene were added to a reactor for reaction at a reaction temperature of 0°C, a stirring speed of 400 rpm, and a reaction time of 6 hours. The reactants were poured into acetone for washing and vacuum filtered at 25°C to obtain functional monomer 2 containing double bonds. Figure 2 As shown in the figure, the peaks of hydrogen chemical shifts (d, e, f, g and h) near the imidazole ring of the imidazole functional monomer 1 containing a double bond are located at 2.07, 9.82, 8.33, 8.08 and 7.36 ppm, respectively, and the hydrogen absorption peak near the imidazole ring has undergone a series of chemical shift changes. Similar changes were observed in the absorption peak of the functional monomer 2 containing a double bond, indicating that the functional monomer has been successfully synthesized.

[0026] Step S3, preparation of cross-linked amino polybenzimidazole solution: add 1000 parts by mass of solvent acetone and 40 parts by mass of amino polybenzimidazole powder to the reactor to dissolve, then add double bond-containing imidazole functional monomer 1, double bond-containing functional monomer 2 and 2 parts by mass of initiator azobisisobutyronitrile in sequence, heat to 70°C for reaction for 5h, then heat to 150°C for reaction for 12h to obtain a cross-linked amino polybenzimidazole solution. Figure 1 As shown, the cross-linked amino-type polybenzimidazole is firstly polymerized into a polymer with a cross-linked structure through substitution reaction and double bonds, and then forms a dense cross-linked structure through substitution reaction.

[0027] Step S4, preparation of cross-linked amino-type polybenzimidazole composite membrane: cast the cross-linked amino-type polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80°C to dry for 18 hours to obtain a cross-linked amino-type polybenzimidazole composite membrane with a thickness of 50 μm. Figure 3 As shown, in order to further determine the structure of the composite membrane, the membrane was tested by infrared spectroscopy (FT-IR), 1533cm -1 The absorption peak at 2853 cm-1 is the characteristic absorption peak of C=N stretching vibration in imidazolium, and the absorption peak at 1640 cm-1 is the characteristic absorption peak of C=C in ionic liquid, indicating that the functional monomer was successfully prepared. -1 and 3376cm -1 The characteristic absorption peak of the stretching vibration at , it can be seen that it was successfully synthesized and cross-linked to the aminobenzimidazole. In summary, the test results show that the cross-linked aminopolybenzimidazole composite membrane was successfully prepared.

[0028] Embodiment 2: comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: 15 parts by mass of compound 1-bromo-3-chloropropane and 14 parts by mass of imidazole compound 2-vinyl imidazole are added to a reactor for reaction, the reaction temperature is 150°C, the stirring speed is 350rpm, and the reaction is continued for 12 hours under condensation reflux conditions. The reactant is poured into acetone for washing and vacuum filtered at 25°C to obtain imidazole functional monomer 1 containing a double bond.

[0029] Step S2, preparation of functional monomer 2 containing a double bond: 8 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 7 parts by mass of compound 1-bromo-3-chloropropane and 15 parts by mass of compound 6-bromo-1-hexene were added to a reactor for reaction at a reaction temperature of 5°C, a stirring speed of 350 rpm, and a reaction time of 5 h. The reactants were poured into acetone for washing and vacuum filtered at 25°C to obtain functional monomer 2 containing a double bond.

[0030] Step S3, preparation of a cross-linked amino polybenzimidazole solution: 1300 parts by mass of dimethyl sulfoxide solvent and 60 parts by mass of amino polybenzimidazole powder were added to a reactor to dissolve, and then imidazole functional monomer 1 containing a double bond, functional monomer 2 containing a double bond and 3 parts by mass of initiator azobisisoheptanenitrile were added in sequence, the temperature was raised to 75°C for reaction for 4 hours, and then the temperature was raised to 140°C for reaction for 10 hours to obtain a cross-linked amino polybenzimidazole solution.

[0031] Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80° C. to dry for 20 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 40 μm.

[0032] Embodiment 3: comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: 20 parts by mass of compound 1-bromo-6-chlorohexane and 20 parts by mass of imidazole compound 4-vinyl imidazole are added to a reactor for reaction at a reaction temperature of 110° C. and a stirring speed of 500 rpm. The reaction is continued for 14 hours under condensation reflux conditions. The reactant is poured into acetone for washing and vacuum filtered at 25° C. to obtain imidazole functional monomer 1 containing a double bond.

[0033] Step S2, preparation of functional monomer 2 containing a double bond: 10 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 10 parts by mass of compound 1-bromo-6-chlorohexane and 20 parts by mass of compound 5-bromo-1-pentene were added to a reactor for reaction at a reaction temperature of 10° C., a stirring speed of 500 rpm and a reaction time of 8 h. The reactants were poured into acetone for washing and vacuum filtered at 25° C. to obtain functional monomer 2 containing a double bond.

[0034] Step S3, preparation of a cross-linked amino polybenzimidazole solution: 2000 parts by mass of solvent N,N-dimethylacetamide and 80 parts by mass of amino polybenzimidazole powder were added to a reactor to dissolve, and then imidazole functional monomer 1 containing a double bond, functional monomer 2 containing a double bond and 4 parts by mass of initiator azobiscyanovaleric acid were added in sequence, the temperature was raised to 80°C for reaction for 6 hours, and then the temperature was raised to 160°C for reaction for 16 hours to obtain a cross-linked amino polybenzimidazole solution.

[0035] Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and dry it in an oven at 80° C. for 24 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 60 μm.

[0036] Embodiment 4: comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: 15 parts by mass of compound 1-bromo-4-chlorobutane and 15 parts by mass of imidazole compound 5-vinyl imidazole were added to a reactor for reaction at a reaction temperature of 90° C. and a stirring speed of 450 rpm. The reaction was continued for 13 hours under condensation reflux conditions. The reactants were poured into acetone for washing and vacuum filtered at 25° C. to obtain imidazole functional monomer 1 containing a double bond.

[0037] Step S2, preparation of functional monomer 2 containing a double bond: 9 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 9 parts by mass of compound 1-bromo-4-chlorobutane and 18 parts by mass of compound 5-bromo-1-pentene were added to a reactor for reaction, the reaction temperature was 8°C, the stirring speed was 450 rpm, the reaction time was 6 h, the reactants were poured into acetone for washing and vacuum filtered at 25°C to obtain functional monomer 2 containing a double bond.

[0038] Step S3, preparation of a cross-linked amino polybenzimidazole solution: 1700 parts by mass of solvent N,N-dimethylformamide and 50 parts by mass of amino polybenzimidazole powder were added to a reactor to dissolve, and then imidazole functional monomer 1 containing a double bond, functional monomer 2 containing a double bond and 3 parts by mass of initiator benzoyl peroxide were added in sequence, the temperature was raised to 60°C for reaction for 6 hours, and then the temperature was raised to 140°C for reaction for 14 hours to obtain a cross-linked amino polybenzimidazole solution.

[0039] Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and dry it in an oven at 80° C. for 20 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 50 μm.

[0040] Embodiment 5: comprises the following steps: Step S1, preparation of imidazole functional monomer 1 containing a double bond: 10 parts by mass of compound 1-bromo-6-chlorohexane and 12 parts by mass of imidazole compound 1-vinyl imidazole were added to a reactor for reaction at a reaction temperature of 120° C. and a stirring speed of 300 rpm. The reaction was continued for 11 hours under condensation reflux conditions. The reactants were poured into acetone for washing and vacuum filtered at 25° C. to obtain imidazole functional monomer 1 containing a double bond.

[0041] Step S2, preparation of functional monomer 2 containing a double bond: 6 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 6 parts by mass of compound 1-bromo-6-chlorohexane and 12 parts by mass of compound 4-bromo-1-butene were added to a reactor for reaction at a reaction temperature of 3°C, a stirring speed of 300 rpm, and a reaction time of 7 h. The reactants were poured into acetone for washing and vacuum filtered at 25°C to obtain functional monomer 2 containing a double bond.

[0042] Step S3, preparation of a cross-linked amino polybenzimidazole solution: 1500 parts by mass of dimethyl sulfoxide solvent and 50 parts by mass of amino polybenzimidazole powder were added to a reactor to dissolve, and then imidazole functional monomer 1 containing a double bond, functional monomer 2 containing a double bond and 2 parts by mass of initiator benzoyl peroxide were added in sequence, the temperature was raised to 75°C for reaction for 3 hours, and then the temperature was raised to 150°C for reaction for 15 hours to obtain a cross-linked amino polybenzimidazole solution.

[0043] Step S4, preparation of cross-linked amino-type polybenzimidazole composite membrane: cast the cross-linked amino-type polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80° C. to dry for 22 hours to obtain a cross-linked amino-type polybenzimidazole composite membrane with a thickness of 50 μm.

[0044] Comparative Example 1 Blank amino polybenzimidazole membrane, the membrane thickness is 50um.

[0045] Comparative Example 2 The same as Example 1, excluding step S1.

[0046] Comparative Example 3 The same as Example 1, excluding step S2.

[0047] 1. Mechanical properties test The mechanical properties of the films of the examples and comparative examples were measured using a SHIMADZUAG-I1KN universal testing machine. The film samples to be tested were cut into 5 mm×50 mm specifications and stretched at a stretching speed of 100 mm / min for mechanical property testing.

[0048] 2. Acid absorption rate experiment The example and comparative example membranes were cut into strips of fixed size and their length, width, thickness and mass were measured. The membranes were then immersed in 5 mol / L potassium hydroxide. After 24 hours, the membranes were taken out, rinsed with deionized water and immersed in deionized water until the alkali solution on the membrane surface was completely removed. In order to remove the moisture on the membrane surface, the membrane was placed in an oven at 110°C. After the moisture was completely removed, the membrane was immersed in phosphoric acid at 90°C. After immersion for 5 hours, the membrane was measured again. The acid absorption rate was calculated by the following formula: Acid absorption rate = (W1-W2) / W2×100% W2 and W1 are the weights of the membrane samples before and after acid absorption, respectively.

[0049] 3. The membrane is assembled into a stack for efficiency testing The embodiment and comparative example membranes were assembled into a stack for testing, and the coulombic efficiency, voltage efficiency and energy efficiency were tested and recorded under the same test conditions. The test results are shown in Table 1: Table 1: Performance test table of the battery stack assembled using the membranes of the embodiment and the comparative example

[0050] It can be seen that the embodiment has a higher tensile strength than the comparative example, because the cross-linked amino polybenzimidazole of the present invention forms a cross-linked structure through substitution reaction and double bond polymerization, thereby improving the tensile strength of the membrane and the mechanical stability of the membrane. In addition, since comparative examples 2 and 3 have a cross-linked structure, but the degree of cross-linking is lower than that of the embodiment, the tensile strength of comparative examples 2 and 3 is higher than that of comparative example 1 but lower than that of the embodiment. The embodiment has a higher acid absorption rate and voltage efficiency than comparative example 1, because the cross-linked amino polybenzimidazole composite membrane of the present invention forms a cross-linked structure through substitution reaction and double bond polymerization, and the functional monomer has an alkaline structure, which can form an acid-base interaction with the acid, thereby improving the acid absorption rate of the composite membrane, so that the membrane obtains a higher acid absorption level, thereby improving the proton conductivity of the membrane, and thereby improving the voltage efficiency of the vanadium battery. The embodiment has a higher coulomb efficiency than comparative example 1, because the nitrogen heterocyclic structure in the cross-linked amino polybenzimidazole composite membrane segment of the present invention has a positive electrical characteristic, and the penetration of vanadium ions can be inhibited by the Donnan exclusion effect, thereby improving the coulomb efficiency of the vanadium battery. Comparative Example 3 has higher acid absorption rate and voltage efficiency than Comparative Example 2. This is because functional monomer 2 has a higher number of neutral nitrogen cations, which is more conducive to increasing the acid absorption rate and improving the voltage efficiency.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries, characterized in that: The following steps are involved: Step S1, preparation of imidazole functional monomer 1 containing a double bond: adding 10-20 parts by weight of compound 1 and 10-20 parts by weight of imidazole compound 2 to a reactor for reaction, pouring the reactants into acetone for washing and vacuum filtering at 25° C. to obtain imidazole functional monomer 1 containing a double bond; Step S2, preparation of a functional monomer 2 containing a double bond: adding 5-10 parts by mass of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5-10 parts by mass of compound 1 and 10-20 parts by mass of compound 3 to a reactor for reaction, pouring the reactants into acetone for washing and vacuum filtering at 25° C. to obtain a functional monomer 2 containing a double bond; Step S3, preparation of a cross-linked amino polybenzimidazole solution: adding 1000-2000 parts by mass of a solvent and 40-80 parts by mass of amino polybenzimidazole powder to a reactor for dissolution, and then sequentially adding an imidazole functional monomer 1 containing a double bond, a functional monomer 2 containing a double bond and 2-4 parts by mass of an initiator for reaction to obtain a cross-linked amino polybenzimidazole solution; Step S4, preparation of cross-linked amino polybenzimidazole composite membrane: cast the cross-linked amino polybenzimidazole solution on a clean glass plate, apply it with a scraper, and place it in an oven at 80° C. to dry for 18-24 hours to obtain a cross-linked amino polybenzimidazole composite membrane with a thickness of 40-60 μm.

2. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: In steps S1 and S2, compound 1 is any one of 1-bromo-3-chloropropane, 1-bromo-4-chlorobutane, and 1-bromo-6-chlorohexane.

3. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: The imidazole compound 2 in step S1 is any one of 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole and 5-vinylimidazole.

4. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: The reaction conditions in step S1 are reaction temperature of 80-150° C., stirring speed of 300-500 rpm, and continuous reaction for 10-14 hours under condensation reflux conditions.

5. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: In step S2, compound 3 is any one of 4-bromo-1-butene, 5-bromo-1-pentene, and 6-bromo-1-hexene.

6. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: The reaction conditions in step S2 are reaction temperature 0-10° C., stirring speed 300-500 rpm, and reaction time 5-8 h.

7. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: In step S3, the solvent is any one of dimethyl sulfoxide, acetone, N,N-dimethylacetamide, and N,N-dimethylformamide.

8. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium battery according to claim 1, characterized in that: In step S3, the initiator is any one of azobisisobutyronitrile, azobisisoheptanenitrile, azobiscyanovaleric acid, benzoyl peroxide, and lauroyl peroxide.

9. The method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries according to claim 1, characterized in that: The reaction conditions in step S3 are to heat to 60-80°C for 3-6 hours, and then heat to 140-160°C for 10-16 hours.

10. A cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries, characterized in that: The composite membrane is prepared by the method for preparing a cross-linked amino-type polybenzimidazole composite membrane for vanadium batteries as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Acid-resistant antioxidant double functional layer composite film and preparation method thereof

    CN122768841A